An environmentally relevant concentration of antibiotics impairs the immune system of zebrafish (Danio rerio) and increases susceptibility to virus infection - Pereiro, Patricia; Rey-Campos, Magalí; Figueras, Antonio; Novoa, Beatriz (Frontiers in Immunology, 2023)
In this work, we analysed the transcriptome and metatranscriptome profiles of zebrafish exposed to an environmental concentration of the two antibiotics most frequently detected in European inland surface water, sulfamethoxazole (SMX) and clarithromycin (CLA). We found that those animals exposed to antibiotics (SMX+CLA) for two weeks showed a higher bacterial load in both the intestine and kidney; however, significant differences in the relative abundance of certain bacterial classes were found only in the intestine, which also showed an altered fungal profile. RNA-Seq analysis revealed that the complement/coagulation system is likely the most altered immune mechanism, although not the only one, in the intestine of fish exposed to antibiotics, with numerous genes inhibited compared to the control fish. On the other hand, the effect of SMX+CLA in the kidney was more modest, and an evident impact on the immune system was not observed. However, infection of both groups with spring viremia of carp virus (SVCV) revealed a completely different response to the virus and an inability of the fish exposed to antibiotics to respond with an increase in the transcription of complement-related genes, a process that was highly activated in the kidney of the untreated zebrafish after SVCV challenge. Together with the higher susceptibility to SVCV of zebrafish treated with SMX+CLA, this suggests that complement system impairment is one of the most important mechanisms involved in antibiotic-mediated immunosuppression. We also observed that zebrafish larvae exposed to SMX+CLA for 7 days showed a lower number of macrophages and neutrophils